PERAN KECERDASAN BUATAN DALAM MENINGKATKAN EFISIENSI PELAYANAN PUBLIK DI INDONESIA - Komarudin , Dedi; Tjenreng, Muhammad Baharuddin Zubakhrum (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This research analyzes the implementation of artificial intelligence (AI) in improving the quality of public services in Indonesia. Using a qualitative method, the study explores the potential, challenges, and optimization strategies of AI in the context of government services. The New Public Service (NPS) theory and e-government concept are used as analytical frameworks to understand how AI can support citizen-centered services. The results show that the Indonesian government has recognized the potential of AI to enhance service efficiency and quality, with implementations such as chatbots for 24-hour information services and data analysis for smart city planning. However, challenges such as the digital divide, infrastructure limitations, and data privacy issues still need to be addressed. The government has taken strategic steps through the National Artificial Intelligence Strategy 2020-2045, digital infrastructure improvement, and the enactment of the Personal Data Protection Act. Nevertheless, further efforts are needed to ensure an inclusive, ethical, and beneficial AI implementation for the entire society. This research concludes that with a comprehensive and collaborative approach, Indonesia has the potential to become a leader in AI adoption in the public sector in the Southeast Asian region.